Game Models on Optimal Strategies in a Tourism Dual-Channel Supply Chain - Lei Yang; Jingna Ji; Kebing Chen (Discrete Dynamics in Nature and Society)
This paper explores a two-echelon tourism supply chain consisting of a hotel and an online travel agency. The upside hotel rooms can be sold through the downside hotel alliance and online travel agency. The hotel alliance, selling rooms at a lower price, is a direct sale platform with a negligible entry fee. Notwithstanding, the online travel agency sells the room at a higher price with related personalized service. Customers will be refunded partially in case of their cancellation or no-show. An integrated model and two decentralized models based on Bertrand and Stackelberg games are developed, respectively. The results show that when the wholesale price is lower than a certain value, both the hotel and the online travel agency can gain more profit from the Stackelberg game than that from the Bertrand game. In the case that the hotel allows overbooking, the optimal overbooking quantity is obtained. If the overbooking proportion is too high, overbooking is profitable for the hotel only when the overbooking cost is lower than a certain value. At the end of the study, some experiments are conducted to analyze the sensitivity of the optimal prices and profits in the light of certain parameters.